BrGDGTs-based temperature and hydrological reconstruction from fluvio-lacustrine sediments in the monsoonal North China Plain since 31 kyr BP. (1st February 2022) - Sun, Minmin; Yang, Shiling; Xiao, Jule; Wang, Yongda; Huang, Xiaofang; Zhang, Shihao; Yang, Xiaoxiao; Jiang, Wenying; Ding, Zhongli
Abstract: Knowledge of glacial-interglacial changes in the East Asian summer monsoon (EASM) can potentially provide insights into future hydrological changes in its region of influence, caused by ongoing global warming. Here, we present temperature and hydrological (soil moisture and pH) reconstructions based on records of branched glycerol dialkyl glycerol tetraethers from fluvio-lacustrine sediments in the monsoonal North China Plain (NCP) for the past 31 kyr. The results show that the air temperature in the NCP was ∼8–9 °C warmer during the mid-Holocene than during the Last Glacial Maximum, and that soil pH is negatively correlated with soil moisture but with a lag of 2–4 kyr due to the buffering effect of carbonates. By contrast, soil moisture increased synchronously with temperature, suggesting that EASM precipitation will increase in the near future as global warming continues. Additionally, the initial increase in land and sea temperature during the last deglaciation lagged summer insolation at northern high latitudes, indicating that insolation was the ultimate trigger of the last deglacial warming. Highlights: BrGDGTs records show a LGM to Holocene warming of ∼8–9 °C in the North China Plain. CBT'-derived soil pH is negatively correlated with precipitation. Soil pH lags 2–4 kyr behind precipitation due to the buffering effect of carbonates. Precipitation increased synchronously with air temperature in the monsoonal China.